(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aims to unveil the nature of human spirit as well as it reflects the transformations that took place in the Omayyad society; which had major influence on the poets’ ways of thinking during that era. These changes have been revealed in the deep and sophisticated thinking which have been featured clearly in the images of character assassination in Yazid Bin Muawiya’s poetry. These images embedded the voice of freedom and the metaphysic inspiration that can penetrate the unconscious sentiments of the human being and reform his distinctiveness in reality. The images of character assassination were the most tangible and credible features that could formulate the genuine identity of the Omayyad society. The poetic images of character assassination have covered a large sphere as an influential and valuable artistic tool in reshaping the real features of the human being in the Omayyad society. These images mark the emerging of the trend of story-telling in the Omayyad poetry which in turn configure distinctive artistic values and disclose the inner human aspects and the matured vision at that time. These images provide us with different sentiments and phases that people have suffered from during the Omayyad era.